A Study on Patient Satisfactionin a Tertiary Care Teaching Hospital Mysore - Sujay Mugaloremutt Jayadeva; Harshith.N (Institute of Medico-legal Publications Pvt Ltd, 2021)
As it’s effortless to enumerate the physical values of the company’s products, as well asthe services, evenso the perceptions of the customeraresomething that really resolves a company’s brand appraisement in amarketplace.Patient satisfaction finds to be crucial for any hospital it not only brings good image to thehospital,but also gives a strong satisfaction and trust for the patient towards the hospitals,this research wascarried out mainly to assess the perceptions of healthcare satisfaction among the patients.100 patients weretaken as sample size in this study and the study was carried out. The data were obtainedfrom the patients bycollecting their reviews based on the questionnaire.Results suggested that a majority of the patients requiredcustomer services as their first preference and also there were only 6 patients who gave the scale of 10 forsatisfaction. so the study concludes that there should be measures taken by the hospital inorder to increasethe patient satisfaction towards the hospital services